Porcine synapsin 1: SYN1 gene analysis and functional characterization of the promoter. Issue 1 (7th October 2013) - Hedegaard, Claus; Kjaer-Sorensen, Kasper; Madsen, Lone Bruhn; Henriksen, Carina; Momeni, Jamal; Bendixen, Christian; Oxvig, Claus; Larsen, Knud
Abstract : Synapsin 1 (SYN1) is a phosphoprotein involved in nerve signal transmission. The porcine SYN1 promoter orthologue was cloned and characterized to provide a means of expressing a transgene specifically in neurons. The nucleotide sequence of the promoter displayed a high degree of conservation of elements responsible for neuron‐specific expression. Expression analysis of SYN1 demonstrated presence of transcript during embryonic development. Analysis of GFP expression in transgenic zebrafish embryos suggests that the pig SYN1 promoter directs expression in neuronal cells. Thus, the SYN1 promoter is a good candidate for use in the generation of pig models of human neurodegenerative disorders. Abstract : The porcine synapsin1 (SYN1) promoter was cloned and characterized. SYN1 mRNA expression is detected in brain during embryo development. The SYN1 gene is mapped to pig chromosome X. Porcine SYN1 directs GFP expression in neuronal cells of transgenic zebrafish.